PENGARUH BIAYA LINGKUNGAN DAN KINERJA LINGKUNGAN DALAM MEMODERASI PENGARUH PROFITABILITAS TERHADAP NILAI PERUSAHAAN - KUSUMA WARDHANA, PRADITYA (Jurnal Akuntansi AKUNESA, 2017)
The purpose of this study is to analize the moderation role of environmental costand environmental performance in affecting the quality of the relationshipbetween profitability and firm value. Observations of the study were conducted atmanufacturing company which is listed on Indonesia Stock Exchange, with athree-year observation period (2014-2016). The research sample was determinedusing purposive sampling method, after selected based on predetermined criteria,the data available for observation was 174. In this study, hypotheses were testedusing moderation regression analysis (MRA). The results obtained from this studyindicate that profitability (P) has a positive effect on firm value (NP),environmental cost (BL) is unable to give a significant influence in moderating therelationship between profitability and firm value, while environmentalperformance (KL) was able to moderate the relationship between profitability andfirm value.